Rare Case of Psychrobacter Sanguinis Bacteremia in a Homeless Patient with Thigh Phlegmon - Bielec Filip; Machnicki Piotr; Mikołajczyk-Solińska Melania; Kasznicki Jacek; Pastuszak-Lewandoska Dorota; Brauncajs Małgorzata (Postępy Mikrobiologii, 2025)
Psychrobacter sanguinis is an emerging opportunistic pathogen predominantly isolated from cold environments that is increasingly recognized for its clinical relevance. This case report documents a rare instance of P. sanguinis bacteremia in a 69-year-old homeless patient presenting with thigh phlegmon. The patient was admitted with elevated inflammatory markers and treated empirically with antibiotics. Blood cultures identified P. phenylpyruvicus, later confirmed as P. sanguinis via 16S rRNA sequencing. Despite initial antibiotic therapy, the patient’s condition necessitated surgical intervention for phlegmon drainage. The antibiotic regimen was adjusted based on susceptibility profiles, leading to gradual clinical improvement. This case underscores the significance of accurate microbial identification in managing infections caused by less common pathogens. The severity of infection was doubtlessly influenced by the patient’s homeless status and associated risk factors, such as poor hygiene and potential environmental exposure. This report highlights the clinical implications of P. sanguinis and the importance of considering environmental pathogens in atypical presentations of bacteremia.